LEGAL IMPLICATIONS OF PRETRIAL DECISIONS OUTSIDE THE OBJECT OF PRETRIAL CONSIDERED IN THE LIGHT OF SUPREME COURT REGULATION NUMBER 4 OF 2016 CONCERNING THE PROHIBITION OF REVIEW OF PRETRIAL DECISIONS - Rahmat Hidayat; Yuliati; Abdul Majid (CV. RADJA PUBLIKA, 2025)
Pretrial decisions have an important role in ensuring the protection of human rights and controlling coercive actions by law enforcement officers in the Indonesian criminal justice system. However, in judicial practice, dynamics have developed where pretrial judges decide cases outside the object of pretrial as limited by Article 77 of the Criminal Procedure Code, such as examining the validity of the determination of suspects, preliminary evidence, and even the main points of the case. This development has given rise to legal issues, especially after the issuance of Supreme Court Regulation (Perma) Number 4 of 2016 which expressly prohibits the legal remedy of Judicial Review (PK) against pretrial decisions. This study aims to analyze: (1) the legal basis for the birth of pretrial decisions that exceed the limits of the object of authority; (2) the legal implications of these decisions on the principles of legal certainty, justice, and due process of law; and (3) the relevance of Perma No. 4 of 2016 in providing solutions to the lack of legal remedies for controversial pretrial decisions. This study uses a normative legal method with a statutory, case, and conceptual approach. The data were analyzed qualitatively through systematic and comparative legal interpretation of pretrial practices following Constitutional Court Decision No. 21/PUU-XII/2014 and other progressive pretrial decisions. The research results show that the expansion of pretrial objects is a consequence of the constitutional interpretation of the protection of the suspect's rights, but at the same time creates legal uncertainty and disharmony between the norms of the Criminal Procedure Code and judicial practice. The prohibition of judicial review in Supreme Court Regulation No. 4 of 2016 limits access to justice by closing the room for correction of ultra vires pretrial decisions. Therefore, it is necessary to reconstruct the pretrial regulations in the future Criminal Procedure Code and open up space for limited legal remedies to prevent abuse of pretrial judges' authority.